ALIENATION OF MAN AS REFLECTED IN JOHN GRISHAM’S THEODORE BOONE: THE ACTIVIST - Fauziah, Hana (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2020)
This article is purposed to reveal alienation of man as reflected in the novel of John Grisham’s entitled Theodore Boone: the Activist. In this paper, alienation is described as the condition when man is separated from his surroundings. This matter occurs due to the replacement of concrete understanding into abstractification. In the novel, abstractification is narrated in the description of treating nature and land for profit orientation. As a result, the alienation of man is shown in his feeling of separation from essential values of humanity. By using the postmodernism approach for this research, the results show that an authority’s policy such as the project of infrastructure without considering the public interest, as told in the novel, will cause not only the damages of environment but also the destruction of the civilization. In this paper, alienation of man is classified into alienation from activity, self-alienation, and alienation from others. Those classifications in the novel are proven to bring human to dehumanization.